Prototype Mesin Cuci berbasis Energi Ramah Lingkungan - Indra Yasri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
Washing machine technology has been developed well in the last ten years, it’s vary from the simple technology until utilizing of artificial  intelligent to improve washing quality and controlling motor to obtain energy efficiency. However the issues of eco-friendly power supply has been not covered by the recent development of technology. The design prototyping of the Mini Washing Machine with the Solar Power is proposed to answer these issues.  This design have specific features such as 0.5 gallon sized of washing capacity, DC voltage based power supply and able to perform the standard operational of washing machine. It is composed by 0.5 gallon sized of bucket, DC motor with 700rpm of maximum speed, washing blade, LI-ion battery and solar panel for LI-ion battery charging power supply. The special connection between dc motor and washing blade are done through combination of axle shaft and different size of double pulleys. Minimum loss of power is achieved by using this connection. The testing result shows the design is successfully operated in 2 modes of motor speed i.e. low speed for light of cloths and high speed for heavy cloths